LEXICONS OF TABUH RAH USED IN MENYALI VILLAGE - Widarta Kusuma, I Made Adi; Budasi, I Gede; Suarnajaya, I Wayan (Universitas Pendidikan Ganesha, 2020)
This study investigated the lexicons used in Tabuh Rah ceremony in Menyali village. This research was designed in the form of descriptive qualitative study. The focus of this study was to find out lexicons that exist in Tabuh Rah ceremony in Menyali village. The data of this study were obtained by conducting observation and interview with three informants who were from from Menyali village. The object of this study was Tabuh Rah lexicons that exist in Menyali village. The result of this study shows that there were seventy-one lexicons existing in Tabuh Rah ceremony in Menyali village. Those seventy-one lexicons were grouped based on their categories, including twelve lexicons which were concerned with series of events, fifteen lexicons dealt with Tabuh Rah facilities, six lexicons were found in roles in Tabuh Rah, three lexicons concerned with Tabuh Rah arena, four lexicons had something to do with kinds of offerings, twelve lexicons related to types of cocks, six lexicons dealt with types of taji pairings and thirteen lexicons were concerned with betting codes. All of the lexicons had their own meaning and function in the ceremony. The villagers kept using Tabuh Rah lexicons during the ceremony in order to maintain the language, especially maintaining Tabuh Rah lexicons in Menyali village.Keywords: Language maintenance, Tabuh Rah ceremony, TabuhÂ